Measuring local government spending efficiency: evidence for the Lisbon region - Afonso, António (2022)
Measuring local government spending efficiency: evidence for the Lisbon region, Regional Studies 40, 39–53. The expenditure efficiency of Portuguese local governments in 2001 was assessed using Data Envelopment Analysis for production frontier estimation. A composite municipal output indicator was constructed and input and output efficiency scores were computed for 51 Portuguese municipalities in the region of Lisbon and Vale do Tejo. This allows a determination of the extent of municipal spending that seems to be ‘wasted’ relative to the theoretical ‘best-practice’ frontier. The results suggest that Vale do Tejo municipalities could achieve, on average, the same level of output allegedly using around one-third fewer resources, improving performance without necessarily increasing municipal spending.